Deciphering the molecular mechanism of tetrandrine in inhibiting hepatocellular carcinoma and increasing sorafenib sensitivity by combining network pharmacology and experimental evaluation - Biao Niu; Sidong Wei; Jianjun Sun; Huibo Zhao; Bing Wang; Guoyong Chen (Taylor & Francis Group, 2022)
Context The mechanism of tetrandrine (TET) in hepatocellular carcinoma (HCC) progression and sorafenib (Sora) chemosensitivity deserves investigation. Objective Using network pharmacology approaches to elucidate the mechanisms of TET in HCC. Materials and methods CCK-8, colony formation, and flow cytometry assays were used to measure cell phenotypes. BALB/c nude mice were divided into Control, Sora (10 mg/kg), TET (50 mg/kg), and TET + Sora (10 mg/kg Sora plus 50 mg/kg TET) groups to evaluate the antitumor effects of TET for 21 days. Sora and TET were given by intraperitoneal injection or oral gavage. Results For SMMC7721 (IC50 = 22.5 μM) and PLC8024 (IC50 = 18.4 μM), TET (10, 20 μM) reduced colony number (0.68 ± 0.04- and 0.50 ± 0.04-fold, 0.56 ± 0.04- and 0.42 ± 0.02-fold), induced cell cycle arrest at G0/G1 stage (1.22 ± 0.03- and 1.39 ± 0.07-fold, 1.37 ± 0.06- and 1.55 ± 0.05-fold), promoted apoptosis (2.49 ± 0.26- and 3.63 ± 0.33-fold, 2.74 ± 0.42- and 3.73 ± 0.61-fold), and inactivated PI3K/AKT/mTOR signalling. Sora (10 μM) decreased cell proliferation, enhanced apoptosis, and inhibited PI3K/AKT/mTOR signalling, and these effects were further aggravated in the combination group. Activating PI3K/AKT/mTOR reversed the effects of TET on cell proliferation and Sora sensitivity. In the combination group, tumour volumes and weights were decreased to 202.3 ± 17.4 mm3 and 151.5 ± 25.8 mg compared with Sora (510.6 ± 48.2 mm3 and 396.7 ± 33.5 mg). Discussion and conclusions TET enhances Sora sensitivity by inactivating PI3K/AKT/mTOR, suggesting the potential of TET as a chemosensitizer in HCC.